2009
DOI: 10.1017/s0950268809990847
|View full text |Cite
|
Sign up to set email alerts
|

Transmission routes and risk factors for autochthonous hepatitis E virus infection in Europe: a systematic review

Abstract: SUMMARYIncreasing numbers of non-travel-associated hepatitis E virus (HEV) infections have been reported in Europe in recent years. Our objective was to review the evidence on risk factors and transmission routes of autochthonous HEV infection and hepatitis E in Europe in order to develop recommendations for future research, prevention and control. A systematic literature review was performed to identify all primary reports and studies published during 1998-2008 on hepatitis E in humans and animals in Europe b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
179
2
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(192 citation statements)
references
References 127 publications
(240 reference statements)
9
179
2
2
Order By: Relevance
“…Studies of wildlife in Poland confirmed that HEV circulates in the wild boar population, which creates a potential risk of virus transmission to domestic animals and humans. Wild boars should be considered an important HEV reservoir with an increasing transmission potential related to their intensively growing population (11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of wildlife in Poland confirmed that HEV circulates in the wild boar population, which creates a potential risk of virus transmission to domestic animals and humans. Wild boars should be considered an important HEV reservoir with an increasing transmission potential related to their intensively growing population (11).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis E virus (HEV), the aetiological agent of hepatitis E, is a member of the Orthohepesvirus genus within the Hepeviridae family and consists of genotypes 1, 2, 3, and 4 which infect humans and other mammals (1,11,20,23). It is a non-enveloped virus, 27-34 nm in diameter, whose genome contains a nonsegmented positive-sense RNA chain (10,23).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So wurden vorsorglich einzelne ELISA-Teste, die eine hohe Rate an falsch-negativen Ergebnissen aufwiesen, vom Markt genommen und durch neue Teste ersetzt [163].…”
Section: Kürzlich Wurden Untersuchungen Zur Reaktivität Von Seren Vonunclassified